THE MAIN TASKS OF THE COMMUNICATIVE APPROACH IN TEACHING ENGLISH - Islomova Latofat Fazliddinovna (Web of Journals Publishing, 2024)
Communicative approach to teaching English is a student-oriented methodology aimed at developing students' ability to communicate effectively in the language. It emphasizes real-life communication, interaction, and practical use of language in various contexts. The main tasks of the communicative approach can be divided into several main areas aimed at improving students' communicative competence and language skills. These tasks include the development of communication, the development of speaking and listening skills, the integration of language skills, the provision of authentic language use, the development of cooperation and interaction, and emphasizing the importance of accuracy. In this article, we Let's consider each of these tasks in detail in order to fully understand the main goals of the communicative approach in teaching English.
Keywords: English language, teaching methodology, grammar, communicative approach, speech, pronunciation.